"Menyuarakan Kewaspadaan Terhadap Hoax: Mengenal dan Melawan Penyebaran Informasi Palsu melalui Pengabdian Masyarakat di Sekolah 'MIN 1 Kota Palangkaraya - Abdul Syahid; Annisa Meilyani; Arya Eka Saputra; Dimas Faqih Rosyidin; Elma Astutie; Marisa Shermia Nandha; Revi Nauval Ilhansyah; Yusuf Yusuf (Jurnal Kabar Masyarakat, 2024)
This community service aims to increase the understanding and awareness of the community, especially students and teachers at 'MIN Satu Kota Palangkaraya' School, about the dangers of spreading hoaxes as well as strategies to identify and deal with them. Hoaxes or false information are increasingly becoming a troubling threat with their ability to spread rapidly through social media and other digital platforms. Through a series of activities such as workshops and discussions, participants will be given an in-depth understanding of the importance of verifying information before disseminating it. In addition, they will also be equipped with critical skills to analyze the content they encounter online. Thus, it is hoped that the community, especially the younger generation who are active users of social media, will become more vigilant and responsible in disseminating information, and be able to distinguish between valid information and hoaxes. By involving schools as the center of education, the project also aims to strengthen digital literacy among students and teachers. As such, they will become effective in combating the spread of hoaxes, and help create a safer online environment filled with accurate and useful information.